Lateral Versus Medial Hallux Excision in Preaxial Polydactyly of the Foot. (December 2020) - Burger, Elise B.; Bus, Sicco A.; Hovius, Steven E. R.; van Nieuwenhoven, Christianne A.
Background: In preaxial polydactyly of the foot, the choice for excision of the lateral or medial hallux is not straightforward, in particular with proximal phalangeal (type IV) and metatarsal (type VI) duplication, because of anatomical characteristics. We evaluated whether medial or lateral hallux excision gives better outcomes in these duplication types, to help clinical decision making. Methods: Children with type IV or type VI duplication (n=14, age: 4.4-17.2 years), who were operatively treated by excision of the lateral or medial hallux, were assessed for foot function using plantar pressure measurements and clinical examination. Foot aesthetics were scored by the child, an expert, and 10 laypersons, and additional patient-reported outcome questionnaires were obtained. Outcomes were compared between lateral and medial excision, per duplication type. Results: In type IV duplication (n=11), lateral excision showed a better distribution of peak pressure between the hallux and first metatarsal with significantly lower median first metatarsal peak pressure ( P = .008). Lateral excision showed more medial hallux deviation ( P = .017). Foot aesthetics were not different between excision sides. In type VI duplication (n=12), lateral excision showed a 59% higher hallux peak pressure, larger medial hallux deviation ( P = .004), and more reoperations. Foot aesthetics were scored significantly better after lateral excision by experts and laypersons. Conclusions: Foot function by virtue of plantar pressure was better after lateral hallux excision in type IV and after medial hallux excision in type VI duplication. Surgeons and laypersons perceived the foot as more normal after lateral excision in type VI, whereas children reported no differences. These outcomes can be used in clinical decision making. Level of Evidence: Level III, therapeutic, comparative study.